Geographies of doing nothing–internal displacement and practices of post-disaster recovery in urban areas of the Kathmandu valley, Nepal - Titz, Alexandra (Social Sciences, 2021)
Disaster-related internal displacement is on the rise in many countries and is increasingly becoming an urban phenomenon. For many people, as in the case of the earthquake disaster 2015 in Nepal, protracted or multiple disaster displacements are a lived reality. While the drivers of displacement are relatively well understood, significant uncertainties remain regarding the factors that trigger prolonged or secondary displacement and impede ending of displacement or achieving durable solutions. The purpose of this article is to illustrate and theorise the discourse of reconstruction and return that shapes experiences, strategies, and policies in order to gain a better understanding of the obstacles to pursuing durable solutions that are still shaping the reality of life for urban internally displaced people (IDPs) in Kathmandu Valley. I use the concepts of ‘fields of practice’ and ‘disaster justice’ to provide insights into the theorisation of the links between social inequality, structural forms of governance, and the reconstruction process itself. Findings demonstrate that the application of these concepts has great potential to expand our understanding of ‘realities of life’ and practices of IDPs, and thus contribute to a more differentiated evidence base for the development and implementation of appropriate disaster risk reduction policies and practices.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Disaster justice; Disaster risk reduction (DRR); Earthquake disaster; Fields of practice; Internal displacement; Long-term displacement; Waiting